(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
In the article, the author examines the regulatory framework governing the status of joint-stock companies, a joint-stock company is considered as a subject of civil law. The instability of the legislation on joint-stock companies is noted.